The clinical approach used in supporting individuals with intellectual disability who have been sexually abused. (8th February 2019) - O'Malley, Grace; Irwin, Lynn; Syed, Akhtar Ali; Guerin, Suzanne
Accessible Summary: Sexual abuse is when someone does something sexual to someone else when they do not want them to. We wanted to find out how people get help after sexual abuse. We learned that talking with a psychologist or with staff helps. It is best if these are people you trust. It is also important that you know that the help will work. How everyone involved in a person's support thinks about the abuse also plays a role in the kind of help a person gets. Abstract: Background: Although sexual abuse (SA) constitutes a significant problem in intellectual disability settings, little is known regarding how services support individuals with intellectual disability who have been abused. Method: Using a qualitative design, we explored how one voluntary community service, and in particular their psychology department, responded when people with intellectual disability presented with a clinical need regarding an abuse history. A collective case study was completed based on triangulated data from the clinical files of six individuals with intellectual disability, and based on nine interviews with individuals and/or informants (i.e., psychologists, staff) regarding the six cases. Results: Thematic analysis indicated psychology's and staff's role in delivering behavioural support and psychotherapy. Themes of trust, confidence and suggestibility are relevant to the therapeutic process in cases of abuse, while factors such as the attitudes of support providers may impact therapeutic engagement. Conclusions: In the absence of a sufficient evidence base in intellectual disability, there is little to guide clinicians working psychotherapeutically with the issue of SA and further research is crucial. While practitioners may perceive particular approaches to be helpful, caution is warranted and feedback from multiple stakeholders is an essential component of safe practice in instances of the delivery of an experimental approach.